On T cell memory: arguments for antigen dependence. - Kündig, T; Bachmann, M; Ohashi, P; Pircher, H; Hengartner, H; Zinkernagel, R (1996)
Memory is a hallmark of the immune system. Considerable progress has been made towards understanding B cell memory, but T cell memory remains poorly understood and its nature is controversial. There is good evidence that B cell memory is driven by antigen, but the antigen dependence of T cell memory is still being debated. For several years we have investigated the nature, duration and antigen dependence of different aspects of CD8+ T cell memory and this review will discuss our findings as well as how and why they differ from some other results. As others, we find that antigen, due to proliferation of antigen-specific T cell clones, induces a shift in the T cell repertoire which remains detectable for years as an elevated cytotoxic T cell precursor frequency (CTLp) in lymphoid organs. Also in the absence of antigen, in vitro assays for T cell memory which invariably isolate memory T cells from these lymphoid organs therefore remain positive. In contrast, immunity against reinfection with a pathogen requires more than just elevated numbers of CTLp in lymphoid organs. Since reinfection usually takes place via peripheral nonlymphoid tissue, these CTLp have to a) efficiently extravasate and patrol through such tissues, and b) be immediately able to exert effector function in case of reinfection. Both functions, require a certain level of activation which critically depends on T cell stimulation by persisting antigen.